Implementing Quality Improvement Management in Madrasah Aliyah - Suriadi Panjaitan; Amiruddin Siahaan; Muhammad Rifa’i (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This article aims to describe the Quality Improvement Management Implementation of the MAS Al Washliyah Mosque in the Village of Kualuh Hilir District, North Labuhanbatu Regency. This study used a qualitative research type, with a naturalistic approach, collecting research data obtained by observation, interview, and documentation techniques. To check the validity of the data using triangulation techniques, namely with credibility, transferability, dependability, and confirmability. The steps for data analysis are using data analysis using the Bogdan model, namely reducing data, presenting data, and then concluding. The results of this study are four findings of this study, namely: 1) As for planning to improve the quality of the MAS Al Washliyah Kampung Mosque, namely increasing the ability of teachers, graduates, and madrasah infrastructure, 2) Organizing resources for improving the quality of education at the MAS Al Washliyah Kampung Mosque dividing the main duties and functions are in accordance with the plans to be carried out, 3) Implementation of Management to improve the quality of education at the MAS Al Washliyah Kampung Mosque according to the results of the research, namely; curriculum review, teacher training and construction of facilities and infrastructure. 4) Direct supervision is carried out by the head of the Madrasah on the implementation of the quality improvement program.